Basics of quantum electrodynamics - Merches, Ioan.; Tatomir, Dorian; Lupu, Roxana E. (Boca Raton : CRC Press, 2013)
"PREFACE Quantum Field Theory was born only several years after Quantum Mechanics, more precisely in 1927, when P.A.M.Dirac performed the quantization of the electromagnetic radiation (Proc.Roy.Soc.A, vol. 114, 1927, pp.243 and 710). Unlike Quantum Mechanics, which became a well established chapter of Theoretical Physics in less than a decade, Quantum Field Theory (QFT) needed two decades to become sufficiently well developed. The explanation is that there were no applications by that time. The crucial role in the development of QFT was played by Bethe's paper (Phys.Rev. vol.72, 1947, p.339) concerning the so-called Lamb shift (or displacement), which is a small difference in energy between two energy levels 2S1/2 and 2P1/2 (in terms of symbolic notation) of the hydrogen atom. Hans Bethe was the first to explain the Lamb shift in the hydrogen spectrum, and he thus laid the foundation for the development of modern quantum electrodynamics. The Lamb shift currently provides a measurement of the fine-structure constant [alpha] to better than one part per million, allowing a precision test of quantum electrodynamics. By Quantum Electrodynamics (QED) one understands the relativistic quantum field theory of electrodynamics. It describes all phenomena that involve interacting charged particles, and it can be viewed as a perturbation theory of the electromagnetic quantum vacuum. Currently, QED represents a vast discipline in the family of quantum theories, and a very efficient instrument for approaching problems in most chapters of physics: elementary particles, atomic nucleus, solid state, etc. For this reason, almost all modern Quantum Mechanics textbooks end with a chapter dedicated to the quantum aspects of electromagnetic interactions"--
Includes bibliographical references and index.
Keywords: Quantum electrodynamics; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Quantum Theory